2017
DOI: 10.1210/jc.2017-01559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex Hormone Treatment on the Metabolic Syndrome in Transgender Individuals: Focus on Metabolic Cytokines

Abstract: The effects of hormonal therapy on different components of the MS are sex-specific and involve a complex interplay of direct hormonal effects, changes in body composition, and metabolic cytokine secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 44 publications
5
61
1
Order By: Relevance
“…Prescribers regularly monitor potential adverse effects of polycythaemia and liver abnormalities, which are recommended in the product information for transdermal testosterone and testosterone undecanoate. Given the role of testosterone and estradiol in modulating lipid levels and insulin resistance, and the fact that increased mortality in transgender individuals appears to be related to cardiovascular disease, it is reasonable that cardiovascular risk factors are monitored periodically. Low estradiol levels often occur, particularly in trans male (female‐to‐male) individuals whose ovaries have been removed, potentially leading to adverse bone and metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribers regularly monitor potential adverse effects of polycythaemia and liver abnormalities, which are recommended in the product information for transdermal testosterone and testosterone undecanoate. Given the role of testosterone and estradiol in modulating lipid levels and insulin resistance, and the fact that increased mortality in transgender individuals appears to be related to cardiovascular disease, it is reasonable that cardiovascular risk factors are monitored periodically. Low estradiol levels often occur, particularly in trans male (female‐to‐male) individuals whose ovaries have been removed, potentially leading to adverse bone and metabolic effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study by Auer et al, 24 previously untreated male-to-female transgender patients were studied at baseline and after 12 months of oral estrogen exposure. In response to estrogen, fat mass and the waist:hip ratio decreased, along with TG, TC, and HDL-C [ 11 ]. Another study of E 2 administration in men reported increased HDL-C and TG concentrations after 6 months [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant addition of T prevented the rise of adiponectin [ 31 ]. Likewise, long-term (6 to 12 months) of T treatment in female-to-male transsexual patients decreased adiponectin [ 32 ] as well as leptin [ 11 , 33 ]. Accordingly, T and/or its metabolites can diminish leptin and adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data suggest effects of hormonal alterations on risk of hepatic steatosis and metabolic health in transgender patients. (91,92) Female-tomale transgender patients should be screened for liver abnormalities and polycythemia before initiation of high-dose androgen therapy. (93) Male-to-female transgender patients receiving estrogen therapy should work in coordination with their hepatologist during transition.…”
Section: Accepted Articlementioning
confidence: 99%